Grating and hole-array enhanced germanium lateral p-i-n photodetectors on an insulator platform - Zhou, Hao (2022)
Germanium (Ge) lateral p-i-n photodetectors with grating and hole-array structures were fabricated on a Ge-on-insulator (GOI) platform. Owing to the low threading dislocation density (TDD) in the transferred Ge layer, a low dark current of 0.279 μA was achieved at -1 V. The grating structure enhances the optical absorption by guiding the lateral propagation of normal incident light, contributing to a 3× improved responsivity at 1,550 nm. Compared with the grating structure, the hole-array structure not only guides the lateral modes but also benefits the vertical resonance modes. A 4.5× higher responsivity of 0.188 A/W at 1,550 nm was achieved on the 260 nm Ge absorptive layer. In addition, both the grating and the hole-array structure attribute to a 2× and a 1.6× enhanced 3dB bandwidth at -5 V due to significantly reduced capacitance. The planar configuration of - - photodiodes is favorable for large-scale monolithic integration. The incorporated surface structures offer promising approaches to reinforce the responsivity and bandwidth simultaneously, paving the way for the development of high-performance Ge photodetectors on silicon substrate.